Protocol optimization: A comparative study on phylloplane microbial recovery - S.A. Pavithra; S.S. Veena; Aundy Kumar; K. Krishnaveni; B. Lohitha; S. Divya; Beegam Nazrin; Tom Cyriac; S.U. Shilpa; S. Karthikeyan; M.L. Jeeva; R. Arutselvan; et al. (JOURNAL OF ROOT CROPS, 2025)
Abstract Elephant foot yam (Amorphophallus paeoniifolius), a herbaceous perennial crop utilizing the C3 photosynthetic pathway and belonging to the family Araceae, is cultivated extensively across eight Indian states. Despite its numerous agronomic and economic benefits, the crop is vulnerable to several diseases. In recent years, symptoms such as yellowing of foliage, the appearance of various types of spots, and eventual partial or complete wilting have been increasingly observed. This disease, provisionally termed ‘leaf and pseudostem rot’, has been associated with the presence of more than three different pathogens. Investigating the crop’s microbiome, particularly the phylloplane, offers potential for use in biological disease management and may provide deeper insights into the complex etiology of the disorder. In the present study, two protocols were evaluated for isolating phylloplane-associated microbes to determine which method could capture greater microbial diversity. The first protocol involved a single wash of leaf samples, followed by serial dilution and spread plating. The second protocol employed five successive washes of the leaf samples, after which the wash solutions were centrifuged to collect distinct pellets for bacterial and fungal isolation. These pellets were then serially diluted and cultured using dilutions up to 10-10. Results indicated that the second protocol was more effective, yielding a greater number and diversity of microorganisms compared to the direct aliquot method. The fungal and bacterial colony-forming units (CFUs) obtained using the first method were 2.0 × 104 and 9.7 × 105, respectively. In contrast, the five-wash protocol yielded 1.0 × 105 fungal CFUs and 1.0 × 1010 bacterial CFUs. These findings suggest that the sequential washing and centrifugationapproach is more efficient for capturing the microbial diversity present on the leaf surface. Keywords: Elephant foot yam, Phylloplane, Microbiome, Leaf yellowing, Leaf rot